2020
DOI: 10.34172/npj.2021.09
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of remote ischemic preconditioning on serum cystatin C-based acute kidney injury in patients undergoing coronary angiography; a randomized controlled trial

Abstract: Introduction: Contrast-induced acute kidney injury (CI-AKI) is a known complication of cardiac interventions. Remote ischemic preconditioning (RIPC) is a non-pharmacological method which has a nephroprotective effect. Serum cystatin C (CysC) is a suitable biomarker for the early diagnosis of AKI. Objectives: This study aimed to evaluate the incidence of CI-AKI after RIPC in patients undergoing coronary angiography, through assessment of CysC. Patients and Methods: Around 140 patients with stable coronary arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Scholars such as Al-Beladi [ 10 ] have found through experiments that serum Cys C can diagnose acute renal injury 1.5 d–2 d earlier than SCr. Moradkhani et al [ 11 ] also confirmed that Cys C can be used as an early diagnostic indicator of acute kidney injury associated with sepsis in children. In this study, we divided 67 children with severe sepsis into three groups according to the time interval from the time point of serum Cys C >15 mg/L to the time point of CBP initiation.…”
Section: Discussionmentioning
confidence: 95%
“…Scholars such as Al-Beladi [ 10 ] have found through experiments that serum Cys C can diagnose acute renal injury 1.5 d–2 d earlier than SCr. Moradkhani et al [ 11 ] also confirmed that Cys C can be used as an early diagnostic indicator of acute kidney injury associated with sepsis in children. In this study, we divided 67 children with severe sepsis into three groups according to the time interval from the time point of serum Cys C >15 mg/L to the time point of CBP initiation.…”
Section: Discussionmentioning
confidence: 95%
“…Some studies have found that Cys-C has a diagnostic and predictive role in sepsis complicated with acute kidney injury (SA-AKI). Cys-c can diagnose SA-AKI in advance than creatinine and is more suitable as a biomarker of sepsis and complications than creatinine (Figure 3) [28].…”
Section: Severe Infectious Inflammatory Diseasementioning
confidence: 99%